Integrative approach reveals two new species of Obama (Platyhelminthes: Tricladida) from the South-Brazilian Atlantic Forest - Marques, Alessandro; Rossi, Ilana; Valiati, Victor Hugo; Leal-Zanchet, Ana Maria (Zootaxa, 2018)
The genus Obama Carbayo et al., 2013 includes 38 species, being the most species-rich within Geoplaninae. Species of this genus show a similar anatomy regarding their copulatory apparatus, which may hinder species differentiation. In this study, we describe two new species, presenting a marbled colour pattern, found in two different phytophysionomies of the Atlantic Forest, namely Semi-deciduous Forest and Araucaria Forest. Both species can be distinguished from their congeners, as well from each other, by colour pattern and eye arrangement combined with characteristics of the pharynx, penis papilla and prostatic vesicle, confirmed by molecular analyses from cytochrome c oxidase subunit I gene (COI). Phylogenetic analyses suggest that both species herein studied are closely related to another species that occurs in areas of Araucaria Forest (O. maculipunctata). Results also indicate the need to use at least 600 bp of the gene COI in the definitions of interspecific divergences and for species delineation, at least for the genus Obama.